Microwave Absorption Properties Of Single And Double-layer Coatings Based On Strontium Hexaferrite And Graphite Nanocomposite - Siti Nor Ain Rusly; Khamirul Amin Matori; Ismayadi Ismail; Zulkifly Abbas; Zaiki Awang; Muhammad Misbah Muhamad Zulkimi; Fadzidah Mohd Idris; Mohd Hafiz Mohd Zaid; Nor Dalilah Zulfikri (Springer Nature Switzerland AG, 2024)
The microwave absorption properties of single- and double-layer doped strontium hexaferrite (SrCoZnFe16O27) and graphite nanocomposite were investigated. W-type SrCoZnFe16O27 nanoparticles was prepared via solid state reaction using high energy ball milling and sintered at different sintering temperatures. Microwave absorption properties of single- and double-layer structures of different thicknesses were investigated in the frequency range of 8–18 GHz using a network analyzer, and their behavior analyzed based on electromagnetic transmission line theory. The results show that double-layer absorbing material showed better microwave absorption properties than single-layer. Double-layer absorbing material which consisted of graphite as the matching layer and SrCoZnFe16O27 as the absorbing layer demonstrated higher reflection loss values of − 19.5 dB when both layers were 1 mm thick. The bandwidth corresponding to the reflection loss below − 10 dB (i.e. 90% absorption) was 3.8 GHz (11.0–14.8 GHz). The excellent microwave absorption properties of double-layer structures were influenced by good impedance match, multiple internal reflections and coupling interactions between the matching and absorbing layers.